Incidencia de los medios electrónicos en el campo contractual colombiano (2007)
This article deals with the incidence of electronic means in the Colombian contractual system, which, in turn, from the perspective of the form, or formation of the contract, is compared with common elements of legal systems like the Spanish, in the context of the efforts of harmonization and unificationthat are being made by the European Union.